Preliminary report on the new comparative-historical phonology and etymological dictionary of Southern Cushitic - Takács, Gábor (Lingua Posnaniensis, 2021)
The paper offers a preliminary report of the current research for a monographic comparative-etymological elaboration of the Southern Cushitic lexical stock with its uniquely archaic consonantism set in its ancient Afro-Asiatic context. The project is based on the author’s studies over more than two decades by now.